Cognitive impairment following maternal separation in rats mediated by the NAD+/SIRT3 axis via modulation of hippocampal synaptic plasticity - Keke Hao; Fashuai Chen; Shilin Xu; Ying Xiong; Rui Xu; Huan Huang; Chang Shu; Yisheng Lv; Gaohua Wang; Huiling Wang (Translational Psychiatry)
Abstract Maternal separation (MS) during early life can induce behaviors in adult animals that resemble those seen in schizophrenia, manifesting cognitive deficits. These cognitive deficits may be indicative of oxidative stress linked to mitochondrial dysfunction. However, there is limited understanding of the molecular mechanisms regulating mitochondria in neural circuits that govern cognitive impairment relevant to schizophrenia, and their impact on neuronal structure and function. A 24-h MS rat model was utilized to simulate features associated with schizophrenia. Schizophrenia-associated behaviors and cognitive impairment were assessed using the open field test, pre-pulse inhibition, novel object recognition test, and Barnes maze test. The levels of mitochondrial proteins were measured using western blot analysis. Additionally, alterations in mitochondrial morphology, reduced hippocampal neuronal spine density, and impaired LTP in the hippocampus were observed. Nicotinamide (NAM) supplementation, administration of honokiol (HNK) (a SIRT3 activator), or overexpression of SIRT3 could inhibit cognitive deficits and cellular dysfunction. Conversely, administration of 3-TYP (a SIRT3 inhibitor) or knocking down SIRT3 expression in control rats led to deficits in behavioral and hippocampal neuronal phenotype. Our results suggest a causal role for the NAD+/SIRT3 axis in modulating cognitive behaviors via effects on hippocampal neuronal synaptic plasticity. The NAD+/SIRT3 axis could be a promising therapeutic target for addressing cognitive dysfunctions, such as those seen in schizophrenia.